An HBT-based fluorescent probe for nitroreductase determination and its application in Escherichia coli cell imaging. (18th September 2020) - Yang, Quanzhi; Wen, Yujie; Zhong, Aiguo; Xu, Jian; Shao, Shijun
Abstract : HBTPN exhibited excellent performance such as rapid response time, large Stokes shift, good selectivity and sensitivity, and long-wavelength emission. Abstract : A novel HBT-based fluorescent probe HBTPN was reasonably designed for detecting nitroreductase by merging 4-nitrobenzyl as a sensing moiety to HBT-based dye HBTPP . Experiments showed that probe HBTPN displayed a selective and sensitive "turn-on" response towards nitroreductase and has been applied for sensing nitroreductase in live Escherichia coli .